Potential sovereign Sukuk issuances by the United Kingdom government: A critical analysis - Mohamed Ismail, Mohamed Ayaz (2008)
This paper analyses the potential issuance of sovereign Sukuk by the UK government. Islamic lending transactions are governed by the percepts of the Shariah, which bans interest and stipulates that income must be derived as return from entrepreneurial investment. The Islamic debt security known as Sukuk is gaining prominence, as can be seen from the rapid growth of its market, where it is no longer sticking to its niche in Muslim countries and is now penetrating the major western financial markets. Nevertheless, there are numerous issues that threaten the growth of the market and could impede the acceptance of the Sukuk as a viable alternative to conventional bonds, as evident from Sukuk issues that lack in respect of Shariah compliance and declared incompliant by Islamic scholars in various jurisdictions. This paper concludes by discussing a number of critical factors that the UK government should take into consideration when eventually issuing its Sukuk.